Overexpression of Krüppel-Like Factor 4 Suppresses Migration and Invasion of Non-Small Cell Lung Cancer Through c-Jun-NH2-Terminal Kinase/Epithelial-Mesenchymal Transition Signaling Pathway - Wu, Yanping; Lin, Lianjun; Wang, Xiang; Li, Yong; Liu, Zhonghui; Ye, Wei; Huang, Weiming; Lin, Gang; Liu, Haibo; Zhang, Jixin; Li, Ting; Zhao, Beilei; et al. (Frontiers in Pharmacology, 2020)
Krüppel-like factor 4 is a transcription factor and plays a vital role in the cancer initiation and development. However, the role of Krüppel-like factor 4 in the metastasis of non-small cell lung cancer is not clear. Here, we demonstrated that the expression of Krüppel-like factor 4 was significantly decreased in human non-small cell lung cancer tissues compared with that in normal tissues using Western blot. We performed immunohistochemical staining and observed the decreased expression of Krüppel-like factor 4 in human lung cancer tissues, and metastatic tumor tissues located in the trachea and main bronchus. We also found that the E-cadherin expression was decreased, while vimentin expression was increased in human NSCLC tissues and metastatic tumor tissues located in the trachea and main bronchus. Additionally, enforced expression of Krüppel-like factor 4 in mouse lungs significantly inhibited the metastasis of circulating Lewis lung carcinoma cells to the lungs by attenuating MET. Furthermore, cell scratch assays and Matrigel invasion assays revealed that overexpression of Krüppel-like factor 4 inhibited the migration and invasion of non-small cell lung cancer cell lines A549, H1299, H226 and H1650 cells. Moreover, overexpression of Krüppel-like factor 4 attenuated TGF-β1-induced EMT in A549, and inhibited the phosphorylation of JNK, an important pathway in metastasis in non-small cell lung cancer. Our in vivo and in vitro findings illustrate that Krüppel-like factor 4 inhibited metastasis and migration of non-small cell lung cancer, and indicate that Krüppel-like factor 4 could be a potential therapeutic target for the treatment of non-small cell lung cancer.